Genesis problem of philosophical thought in spanish historiography - ANTONOVA, N.V.; MYAGKOV, G.P.; NIKOLAEVA, O.A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The paper concentrates the reader’s attention to the origin and development of the Spanish historic-philosophical tradition. The paper introduces the names of outstanding researchers and their direct mentors in the suggested scientific area who gave a certain impulse for investigating a philosophical thought in Spain. Special attention is paid to the main academic centers that contributed greatly to the Spanish history theory of philosophy and rational thought as a science, revealing their characteristic features. Finally, the paper centers around a challenging dilemma for the Spanish intellectual elite whether to protect the idea of national philosophical thought or to deny it.RESUMEN La formación de la nación civil es la tarea más importante para cualquier estado relacionado con la identidad totalmente civil. Rusia enfrenta serios problemas etnoculturales relacionados con la formación de la identidad lingüística y la identidad civil. A nivel teórico, este trabajo investiga la cuestión de los factores importantes de una política lingüística equilibrada en los estados multinacionales y la preservación de la identidad lingüística. La dimensión lingüística de la globalización tiene en cuenta la política lingüística constructiva con respecto a las lenguas de las minorías nacionales y las formas destructivas de interacción lingüística causadas por la economía y la política.